POLA KARIER PNS, MAMPUKAH MEMOTIVASI PNS? - SE., MSi, AGUSTINUS SULISTYO TP, (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2010)
There are two career paths in management of civil servant in Indonesia, i.e. structural and functional path. Both of these paths have plus or minus point. In attaining organizational goals, both career paths have to be developed and be maintained altogether. An important matter in developing and maintaining structural and functional path is compatibility between competency and demand of each position, either for structural or functional position. Besides, career paths development and management should correspond to personnel as well as organizational expectation.